Protective effect of andrographolide against ulcerative colitis by activating Nrf2/HO-1 mediated antioxidant response - Shu, Long; Fu, Hangjie; Pi, Aiwen; Feng, Yuliang; Dong, Hui; Si, Caijuan; Li, Songtao; Zhu, Feiye; Zheng, Peifen; Zhu, Qin (Frontiers in Pharmacology, 2024)
Ulcerative colitis (UC) is a recurring inflammatory bowel disease, in which oxidative stress plays a role in its progression, and regulation of the oxidative/antioxidative balance has been suggested as a potential target for the treatment of UC. The aim of this study was to evaluate the protective effect of andrographolide against UC and its potential antioxidant properties by modulating the nuclear factor erythroid 2-related factor 2 (Nrf2)/ heme oxygenase-1 (HO-1) pathway.Dextran sulfate sodium (DSS) -induced UC mice and the LPS-induced HT29 inflammatory cell model were established to uncover the potential mechanisms of andrographolide. ML385, a Nrf2 inhibitor, was used in both models to assess whether andrographolide exerts a protective effect against UC through the Nrf2/HO-1 pathway.The in vivo experiment showed that andrographolide ameliorated the symptoms and histopathology of DSS-induced mice and restored the expressions of ZO-1, Occludin-1 and Claudin-1. Meanwhile, DSS-induced oxidative stress and inflammation were suppressed by andrographolide treatment, along with the upregulation of key proteins in the Nrf2/HO-1 pathway. In vitro experiments showed that andrographolide attenuated LPS-induced excessive generation of ROS in HT29 cells, reduced inflammatory factors, and upregulated the expression of proteins related to tight junctions and Nrf2/HO-1 pathway. In addition, ML385 abolished the beneficial effect of andrographolide. In conclusion, the protective effect of andrographolide against UC may involve the suppression of oxidative stress and inflammation via the Nrf2/HO-1 pathway.